Experiencing Illness and the Sick Body in Early Modern Europe - Stolberg, M. author. aut Link
VI, 292 p.
Keywords: Based on thousands of letters written by patients and their relatives and on a wide range of other sources, this book provides the first comprehensive account of how early modern people understood, experienced and dealt with common diseases and how they dealt with them on a day-to-day basis.